1989
DOI: 10.1111/j.1744-7348.1989.tb02103.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem canker (Rhizoctonia solani) on five early and seven maincrop potato cultivars. II Effects on growth and yield

Abstract: In 1983 and 1984, potato seed tubers of five early and seven maincrop cultivars were inoculated with cultures of Rhizoctonia solani during planting in field experiments to simulate severe seed infection. The size of foliage was assessed during June-August and tuber yields recorded during growth and at harvest in October.Stem canker delayed shoot emergence, decreased the number and length of stems and caused increased variation in stem length; these effects were greatest with Maris Peer and Arran Comet (early c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In similar experiments in 1983 and 1984 we compared the incidence and severity of disease and its effects on growth and yield on five early and seven maincrop cultivars. Results are reported here and in Hide, Read, Firmager & Hall, 1989.…”
Section: Introductionmentioning
confidence: 93%
“…In similar experiments in 1983 and 1984 we compared the incidence and severity of disease and its effects on growth and yield on five early and seven maincrop cultivars. Results are reported here and in Hide, Read, Firmager & Hall, 1989.…”
Section: Introductionmentioning
confidence: 93%
“…Similar discrepancies have emerged when the effect of stem canker on yield is considered. Weinhold et al (1982) showed that the severity of stem canker can be directly linked to a reduction in the yield of progeny tubers, but this finding was not supported by Frank (1978) and Hide et al (1989b), who demonstrated the problems of predicting the amount of yield loss from stem canker. It has been suggested that yield is not affected by R. solani infection, even when severe stem canker is present in the growing crop (Small, 1943(Small, , 1945Van Emden et al, 1966).…”
Section: Introductionmentioning
confidence: 95%
“…Read et al (1989) and Hide et al (1989) reported that severe infection of potato plants by R. solani delayed shoot emergence and increased the variability in stem height and weight of foliage. Similarly, Back et al (2006) reported a The experiment also revealed that high initial G. pallida population densities have an effect on R. solani disease incidence and severity of potato.…”
Section: Discussionmentioning
confidence: 99%